Middle East and North Africa Economic Update, October 2019 : Reaching New Heights - Promoting Fair Competition in the Middle East and North Africa - Arezki, Rabah; Ait Ali Slimane, Meriem; Barone, Andrea; Decker, Klaus; Detter, Dag; Fan, Rachel Yuting; Nguyen, Ha; Miralles Murciego, Graciela; Senbet, Lemma (Washington, DC: World Bank, 2019)
Part I of this report discusses the short- and medium-term growth prospects for countries in the Middle East and North Africa (MENA). The region is expected to grow at a subdued rate of 0.6 percent in 2019, rising to 2.6 percent in 2020 and 2.9 percent in 2021. The growth forecast for 2019 is revised down by 0.8 percentage points from the April 2019 projection. MENA’s economic outlook is subject to substantial downside risks—most notably, intensified global economic headwinds and rising geopolitical tensions. Part II argues that promoting fair competition is key for MENA countries to complete the transition from an administered to a market economy. Part II first examines current competition policies in MENA countries and to promote fair competition calls for strengthening competition law and enforcement agencies. It also calls for corporatizing state-owned enterprises, promoting the private sector and creating a level-playing field between them. Any moves to reform MENA economies would be aided by professional management of public assets, which could tap into a new source of national wealth.